Fitness improvements of young soccer players after high volume or small sided games interventions - Hůlka, Karel; Strniště, Matej (Biology of Sport, 2021)
The main goal was to determine anaerobic and aerobic improvement of young soccer players after six-week high volume (HVT) or small sided games (SSG) training intervention. One hundred and one highly trained youth soccer players (16.2 ± 1.3 years) were divided into SSG (n = 51) and HVT groups (n = 50) and according to age into an under sixteen subgroup (U16), under seventeen subgroup (U17), and under nineteen subgroup (U19). The performance was assessed by Yo-Yo intermittent test, Repeated sprint ability test (RSA), and K-test before and after both training interventions. For U16 the SSG group recorded significant improvements in the K-test (0.64 ± 0.56 s; p = .04) and RSA (0.15 ± 0.43 s; p = .01). For U19 the SSG group recorded the same improvements, in the K-test (0.43 ± 0.57 s; p = .007), RSA (0.21 ± 0.22 s; p = .048), and Yo-Yo test (127.25 ± 17.87; p = .049). HVT improved aerobic performance when the Yo-Yo test was significantly better after intervention at U17 (199.00 ± 111.83 m; p = .030), U19 (88.40 ± 66.38 m; p = .049). In total, the HVT group spent 621 min (56.45 ± 5.01 min) of aerobic training and the Small sided game group spent 291 min (26.45 ± 8.61 min) of small sided games focused on aerobic performance. This study showed that both SSG and HVT training interventions were effective for aerobic improvement for the U19 category, but not for younger players. SSG was identified to be more appropriate to fitness development of soccer players.